Improving the Skills of the Subak Giri Kusuma Tirta Group in Mengani Village, Bangli, in Processing Waste into Quality Organic Fertilizer - Astiari, Ni Komang Alit; Sutapa, I Gede; Suaria, I Nengah; Andriani, Anak Agung Sagung Putri Risa; Rama, Kade Nusde Sari (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2025)
This community service program aimed to empower the "Subak Giri Kusuma Tirta" farmer group in Mengani Village, Bangli, by equipping them with the knowledge and skills to produce high-quality liquid organic fertiliser from waste. The ultimate goal was to improve the quality of their intercropped plants. The activity was implemented in two key stages: a theoretical and practical training session on waste processing, and a final evaluation through a post-test questionnaire. The training was met with strong enthusiasm, with participants actively engaging in discussions and demonstrations. The findings indicated a substantial improvement in participant knowledge, as 95% of respondents reported a full understanding of the material and methods presented. The survey also showed high levels of satisfaction, with 85% of the 15 participants expressing great satisfaction with the training. Notably, 100% of the farmer group expressed interest in applying this new technology to their own farms, signifying a strong motivation to adopt sustainable practices. This successful intervention offers a replicable model for enhancing agricultural quality through effective waste management. Contribution to Sustainable Development Goals (SDGs):SDG 2: Zero HungerSDG 12: Responsible Consumption and ProductionSDG 13: Climate ActionSDG 15: Life on Land